Klug-entscheiden-Empfehlungen in der Angiologie - Müller, Oliver J.; Sternitzky, Reinhardt (Der Internist, 2017)
BackgroundThe Choosing wisely initiative addresses measures of high medical impact which are frequently not appropriately performed according to expert opinion.ObjectiveTo increase the quality of indications by providing supportive information on diagnostic and therapeutic measures in the field of angiology.Materials and methodsAs part of the Choosing wisely initiative, the German Society of Angiology has constructed five positive recommendations on underused measures and five negative recommendations concerning those possibly overused. The recommendations were validated by the twelve professional societies of the German Society of Internal Medicine in a consensus conference.Results and discussionThe recommendations cover a broad spectrum of diagnostic and therapeutic modalities, such as the role of ultrasound examinations in vascular diseases, screening for abdominal aortic aneurysms, diagnosis and therapy of peripheral artery disease (PAD), investigation of chronic ulcers, therapy of varicosis, and finally, the problems associated with using anticoagulants in PAD or thrombosis. By discussing the evidence, we aim to demonstrate that not all medically possible measures are actually appropriate in every situation.